PELATIHAN PEMBUATAN BIBIT PISANG BEBAS PENYAKIT LAYU DAN PEMUPUKAN BERIMBANG TANAMAN KAKAO DI DESA BAJRA KECAMATAN SELEMADEG TABANAN - Supadma, A.A.N.; Arthagama, D.M.; Adnyana, I M.; Puja, I N.; Dana, M.; Mega, I M. (Buletin Udayana Mengabdi, 2016)
Cultivation of banana plant at Dusun Menunggul, Desa Bajra, Kecamatan Selemadeg, Tabanan regency, were relatively non intensified. Famers did not know plant cultivation, exact fertilization dosage, banana and cacao deseases, and banana seedling free deseases (free Pseudomonas solanacearum and Fusarium oxysporum). In this activity the community services tems transferred to the famers some informations technology about cultivation of banana plant, soil fertility, fertilization for banana, pest of cacao plant and demonstration about application Biota L and Persada for seedling banana plant, application Diamond Intres Grow petiside for pest of fruit cacao. The result of this short course conducted in Dusun Menunggul on 23 Agustus 2015 with 45 attendants was ecxiting because most farmers were interested in the course substances and materials training, they understand and be able how to treat and apply Biota L and Persada for seedling of banana plant.
Keywords: seedling; deseases of banana; pest of cacao fruit; fertilization dosage